Seasonal Patterns and Trends of Air Pollution in the Upper Northern Thailand from 2004 to 2018 - Sarawut Sukkhum; Apiradee Lim; Thammasin Ingviya; Rattikan Saelim (Aerosol and Air Quality Research)
Abstract The seasonal patterns and trends of air pollutants can be used in assessments of air quality, facilitating authorities’ decisions on policies for monitoring and managing. The objective of this study was to investigate the seasonal patterns and trends of air pollutants in the upper northern Thailand (UNT) from 2004 to 2018. The hourly air pollutant concentration data including carbon monoxide (CO), nitrogen dioxide (NO2), nitrogen oxide (NOx), sulfur dioxide (SO2), ozone (O3), and particulate matter ≤ 10 µm (PM10) recorded from 6 monitoring stations in the UNT were obtained from the Pollution Control Department, Ministry of Natural Resources and Environment of Thailand. Cubic splines were used to assess seasonal patterns and trends of the air pollutants. Linear regression was used to estimate the average increase in concentrations of air pollutants at each monitoring station. The results exhibited seasonal patterns for CO, NOx, NO2, O3 and PM10, in all stations while SO2 exhibited seasonal patterns only in one station in Lampang and all stations in Chiangmai. The concentrations of these pollutants rose during August and September and reached peak levels in March. In the past 15 years, the levels of overall CO, O3 and SO2 in the UNT had significantly increased, on average by 0.015 ppm, 0.012 ppb and 0.015 ppb, respectively. In contrast, NO2, NOx and PM10 had significantly decreased on average of −0.010 ppb, −0.008 ppb and −0.011 µg m−3, respectively. The results provide information to the authorities for setting up proper measures and policies to control and mitigate air quality impacts especially in the dry season.